EFFECTIVENESS OF LACTIC ACID BACTERIA SOLUTION CHALLENGE TEST BY USING DIFFERENT ENVIRONMENTAL CONTROLS CAVENDISH BANANA PEEL FERMENTATION RESULTS AGAINST MACKEREL FISH REVERSE BACTERIA - Reza Salsabila; Evi Liviawaty; Junianto Junianto; Rusky Intan Pratama (Universitas Mataram, 2024)
Mackerel has an economical price, high market demand, and high catch yields so that it is widely used by the wider community compared to other types of pelagic fish, but it has disadvantages, namely that it is highly perishable because after being caught, the fish still undergoes a series of change processes before becoming rotten. Lactic acid bacteria can be applied to preserve fishery products by immersing them in a culture of lactic acid bacteria derived from fermentation. Cavendish banana peel fermentation contains secondary metabolite compounds that have the potential to be antimicrobial, anticancer and antidemartosis. Cavendish banana peels contain flavonoids, alkaloids, tannins, saponins and quinones. This research aims to determine the concentration of environmental controls between salt and vinegar in the Lactic Acid Bacteria fermentation solution from Cavendish banana peels which can provide effectiveness. lactic acid bacteria against mackerel spoilage bacteria. This research was carried out at the Fishery Products Processing Laboratory, Faculty of Fisheries and Marine Sciences, Padjadjaran University in January 2024. This research was carried out by testing Lactic Acid Bacteria from the fermented solution of Cavendish banana peels and spoilage bacteria from mackerel that was soaked for 15 minutes. using paper discs with 3 treatments and 9 repetitions. Observations were made at the 48th hour after incubation at a storage temperature in an incubator of 37oC covering the diameter of the clear zone around the paper disc. The calculation results for estimating the addition of the best environmental control concentration were carried out by analyzing the data using the simultaneous F test followed by the Duncan test. The research results show that the best environmental control concentration addition for Cavendish banana peel fermentation as a source of Lactic Acid Bacteria against mackerel spoilage bacteria to extend shelf life is the addition of 3% salt with a pH of 4.4, a clear zone diameter of 21.37 mm and an effectiveness of 34.1% which is categorized as very strong.